In vitro propagation of Dimorphorchis rossii, an endemic and endangered Sabah orchid - Sharon J Spiridrin (2016)
Dimorphorchis rossii is a threatened orchid species which is endemic to Borneo. Forest clearance and fires on its natural habitat and illegal collection by local people contributed to the extinction of this orchid. Application of plant tissue culture acts as an alternative for conservation and agronomic utilization of this precious species. The effect of capsule age (150, 180 and 210 days), effect of basal medium (KC, VW and MS), complex additives (coconut water, tomato juice, potato homogenate, peptone and yeast extract), plant growth regulators (BAP, KIN, IAA and NAA), carbon source (sucrose, fructose, glucose) and light condition (16 hour light, 24 hour light, 24 hour dark) on in vitro seed germination, protocorm proliferation, protocorm growth and development, protocorm-like bodies (PLB) induction from leaf segments were studied. Data was analyzed using ANOVA, t-test and Duncan test. Study on capsule maturity showed that capsule age from 210 days after pollination showed high germination rate (31.31±3.42%) after 30 days of cultured compare to 150 and 180 days. Thus, capsule was taken at 210 days for subsequent study on seed germination. MS basal media gave the highest percentage of germination (78.35±7.22%) after 150 days of cultured and addition of different types and concentrations of carbon sources showed that MS medium contained 2% (w/v) sucrose was an excellent carbon source (69.43±12.25%). For study of complex additives, 10% (v/v) coconut water showed the highest percentage of germination (95.43±2.00%) followed by 10% and 20% (w/v) tomato juice (94.09±1.19% and 93.78±2.70%, respectively). Besides that, the culture also showed optimum germination response (92.30±3.66%) when kept in growth chamber with 16 hour light in MS medium supplemented with 10% (v/v) coconut water and 2% (w/v) sucrose. In protocorms proliferation and shoots development, protocorms within 1.0 mm-2.0 mm size were used as source of explants. In this study, MS basal medium showed the highest protocorm proliferation (20.00±0.41%) and number of protocorm with leaf (25.00±0.44%). These values was enhanced by addition of 0.2% or 0.3% (w/v) yeast extracts for protocorms proliferation (25.00±0.44%) or with 10% (v/v) coconut water for shoots induction (75.00±0.44%) and rooting (65.00±0.49%). For study involved plant growth regulator, 0.5 mg/l KIN showed the highest percentage of protocorm proliferation (26.70±0.45%) while 2.0 mg/l BAP proved to be excellent hormone for inducing shoot development (63.33±0.49%) and 3.0 mg/l IAA for rooting (36.67±0.49%). Acclimatization of D. rossii was also done to observe the survivability of the orchid when planted outside and after about 60 days, 52.00±0.50% plantlets manage to survive. Leaf segments excised from in vitro seedling of D. rossii was used as source of explant for PLBs induction and shoot development. Treatment of 0.2% (w/v), 0.3% (w/v) yeast extract and 10% (w/v) tomato juice gave the highest respond on PLB induction (13.33±0.46%) in which 0.2% (w/v) yeast extract showed the highest mean number of PLB with value of 30.7±12.92. Explant that was able to formed shoot was observed in MS basal media supplemented with 10% (w/v), 20% (w/v) tomato juice and 10% (w/v), 20% (w/v) potato homogenate with the highest percentage about 13.33±0.45%. On the other hand, 2.0 mg/L BAP showed the highest induction of PLBs (13.3±0.46%) while high mean number of new PLBs was 25.00±4.54 in 2.0 mg/l KIN. For shoot developments, only 2.0 mg/l KIN, 3.0 mg/l IAA, 0.5 mg/l NAA and 2.0 mg/l NAA showed response with percentage of 3.33±0.18%. In conclusion, propagation using complex additive showed promising result compare to plant growth regulators based on result obtained.